2016
DOI: 10.1016/j.joca.2016.01.983
|View full text |Cite
|
Sign up to set email alerts
|

The OA Trial Bank: meta-analysis of individual patient data from knee and hip osteoarthritis trials show that patients with severe pain exhibit greater benefit from intra-articular glucocorticoids

Abstract: This IPD meta-analysis demonstrates that patients with severe knee pain at baseline derive more benefit from IA glucocorticoid injection at short-term follow-up than those with less severe pain at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 38 publications
1
56
0
2
Order By: Relevance
“…The therapies for OA patients were mainly to relieve the pain and inflammation [21]. Researches had shown that the important pathological feature of OA contained articular cartilage degeneration, which was largely attributed to apoptosis of chondrocytes [22].…”
Section: Discussionmentioning
confidence: 99%
“…The therapies for OA patients were mainly to relieve the pain and inflammation [21]. Researches had shown that the important pathological feature of OA contained articular cartilage degeneration, which was largely attributed to apoptosis of chondrocytes [22].…”
Section: Discussionmentioning
confidence: 99%
“…An explorative, pre-defined, subgroup analysis will be performed assessing the interaction effects between injections regarding the severity of knee pain at baseline (NRS pain score of > = 7 versus < 7) on the primary outcome [47]. Generalized estimating equations will be used to analyze differences between groups concerning adverse events, medical consumption and medication usage.…”
Section: Subgroup Analysismentioning
confidence: 99%
“…Systematic reviews indicate low quality evidence that intra-articular corticosteroid injections may provide short term pain relief and a small improvement in physical function for up to six weeks in knee osteoarthritis compared with placebo 46. Patients with more severe disease are likely to experience greater improvement 7.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%